The body and gender - Dzwonkowska-Godula, Krystyna; Garncarek, Emilia; Czernecka, Julita (Body and society. Sociology of the body in research and theoretical concepts, 2023)
The authors of this chapter pursue an issue of the body and embodiment from the gender perspective. In this paper, they assume that the body is perceived and functions socially as a gendered body, containing a cultural content of gender. Referring to various concepts applied in the sociology of gender, they demonstrate what a gendered body is and how it reveals itself; what it means for an individual and what its social meaning is.In the first part of the chapter, the issues of body and gender are introduced from the gender perspective; the transformations of gender are also discussed. Further, the authors tackle the issue of a gendered body’s meaning in the context of one’s gender identity, one’s social roles, gendered division of labour as well as gender relations and inequality. They also draw attention to the issue of intersectionality in embodiment and the body as an aesthetic capital of individuals. The subsections of this chapter offer definitions of the key notions relating to the body and embodiment from the perspective of the sociology of gender. The chapter concludes with verifying questions and a list of publications, the reading of which will allow the readers to broaden their knowledge on the discussed topic.